Tìm GTNN của A=(x+y)(x+z). Biết x,y,z >0 và xyz(x+y+z)=1
Cho x,y,z > 0 thỏa Đk : (x+y+z)xyz =1 Tìm GTNN của BT sau :
P = (x+y)(x+z)
Cho x,y,z > 0 thỏa Đk : (x+y+z)xyz =1 Tìm GTNN của BT sau :
P = (x+y)(x+z)
cho x, y, z>0 và xyz=1
Tìm gtnn của P=(x+y)(y+z)(z+x)-2(x+y+z)
tìm GTNN xyz /[x+y]nhân[y+z]nhân[x+z] biết x,y,z>=0
Tìm gtnn của A=(x+y)(y+z) biết x,y,z\(\in\)R và xyz(x+y+z)=1
cho x, y, z> 0 thỏa mãn x+y+z=xyz. Tìm gtnn của p=x+2y+5z
Cho x,y,z>0 và xyz=1. Tìm GTNN của M = \(\frac{1}{x+y+1}+\frac{1}{y+z+1}+\frac{1}{z+x+1}\)
Cho x>0,y>0,z>0, xyz=1
Tìm GTNN
\(P=\frac{x^2\left(y+z\right)}{y\sqrt{y}+2z\sqrt{z}}+\frac{y^2\left(x+z\right)}{z\sqrt{z}+2x\sqrt{x}}+\frac{z^2\left(x+y\right)}{x\sqrt{x}+2y\sqrt{y}}.\)